PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MENGGOLONGKAN HEWAN BERDASARKAN JENIS MAKANANNYA: (Penelitian Tindakan Kelas pada Siswa Tunagrahita Sedang Kelas VII SMPLB YPPC Kota Banda Aceh) (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
This article describes the efforts to improve the ability to classify animals by type of food using image media. at the Banda Aceh State Extraordinary School (SLB) Class VI with mental retardation. Mentally retarded individuals are individuals who are intact, unique and undergo development, according to their age stages, but they have obstacles in intelligence. At school they experience various learning difficulties. This classroom action researchuses qualitative methods, consisting of two cycles. This research is a qualitative research with research subjects in class VII students as many as 5 (five) people. Data analysis used descriptive analysis techniques by comparing the initial conditions with the results achieved in each cycle. The results showed that the use of image media could improve students’ ability to classify animals based on their type of food. At the end of cycle II, the number of students who completed 80% (4 students), not yet completed 20% (1 student) the class average score was 73 compared to the initial condition, namely 63.